A new species of Saprolegnia (Saprolegniales, Straminipila), from a polluted Argentine channel - Steciow, Mónica Mirta (2002)
Saprolegnia variabilis sp. nov. is described from litter (floating twigs, leaves, and roots) in a artificial polluted channel, near a petroleum refinery, in Buenos Aires Province, Argentina. The species is illustrated and compared with other species of the genus. It differs from S. australis in having mature subcentric oospores; the oogonia and the oospores are larger and more variable in shape and size, and the number of oospores is greater. The oogonial stalks are also variable in length and the zoosporangia are very much longer.